2020
DOI: 10.1111/ijfs.14853
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antihypertensive activity of bioactive peptides derived from porcine blood corpuscle and plasma proteins

Abstract: New bioactive peptides with antihypertensive property from red blood corpuscle (RBC) and plasma (PL) hydrolysate fractions of porcine blood were identified. Three peptides with the highest Angiotensin-converting enzyme (ACE) inhibitory activity from RBC, including RBC7 (TPYPCV), RBC15 (VVYPWR) and RBC9 (FLCT), showed IC 50 values of 2.58 AE 0.87, 5.22 AE 2.56 and 6.53 AE 0.34 µM, respectively. By comparison, PL1 (YTFPFH), PL2 (WGHGNPHV) and PL7 (VPLW) from PL displayed higher IC 50 values at 24.12 AE 2.44, 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Aliphatic amino acids (Leu and Ile) were frequently found in the N-terminus of ACE inhibitory peptides, such as peptides from soy protein (LIVTQ and LIVT) and Volutharpa ampullacea perryi (IVTNWDDMEK) . Positively charged amino acids (His) were reported to be a critical residue in the C-terminus tripeptide position of ACE inhibitory peptides, such as fermented milk (LVYPFPGPIH), Tenebrio molitor (YDDGSYKPH), horse gram flour (VTSTGPVGH), and porcine plasma proteins (YTFPFH) . Some studies found that the bulky hydrophobic amino acids with cyclic or aromatic structures at the C-terminus of the peptides show significant ACE inhibitory activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliphatic amino acids (Leu and Ile) were frequently found in the N-terminus of ACE inhibitory peptides, such as peptides from soy protein (LIVTQ and LIVT) and Volutharpa ampullacea perryi (IVTNWDDMEK) . Positively charged amino acids (His) were reported to be a critical residue in the C-terminus tripeptide position of ACE inhibitory peptides, such as fermented milk (LVYPFPGPIH), Tenebrio molitor (YDDGSYKPH), horse gram flour (VTSTGPVGH), and porcine plasma proteins (YTFPFH) . Some studies found that the bulky hydrophobic amino acids with cyclic or aromatic structures at the C-terminus of the peptides show significant ACE inhibitory activity .…”
Section: Discussionmentioning
confidence: 99%
“…32 Positively charged amino acids (His) were reported to be a critical residue in the C-terminus tripeptide position of ACE inhibitory peptides, 48 such as fermented milk (LVYPFPGPIH), 49 Tenebrio molitor (YDDG-SYKPH), 50 horse gram flour (VTSTGPVGH), 50 and porcine plasma proteins (YTFPFH). 51 Some studies found that the bulky hydrophobic amino acids with cyclic or aromatic structures at the C-terminus of the peptides show significant ACE inhibitory activity. 52 Peptides P3 and P12 consist of the aromatic amino acid Tyr (Y), the aliphatic amino Gly (G), and the positively charged and aromatic amino acid His (H) at the C-terminus of the peptide.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therefore, bone and bone‐associated protein‐containing tissues demonstrate considerable potentials as sources for the preparation of calcium‐chelating peptides. Similarly, animal blood is rich in plasma proteins, which are also excellent sources of peptides (Aiemratchanee et al., 2020). Iron is a significant component that plays a role in both the structural properties and functionality of hemoglobin.…”
Section: Sources and Preparations Of Food‐derived Mcpsmentioning
confidence: 99%
“…Furthermore, Aiemratchanee et al. (2021) isolated novel BAPs with antihypertensive characteristics from red blood corpuscle (RBC) and plasma (PL) hydrolysate fractions of swine blood. The IC 50 values of three peptides possessing the highest ACE‐inhibitory activity from RBCs, comprising RBC 7 (TPYPCV), RBC9 (FLCT), and RBC15 (VVYPWR), were 2.58 ± 0.87, 6.53 ± 0.34, and 5.22 ± 2.56 μM, respectively.…”
Section: Health‐promoting Effects Of Food Bapsmentioning
confidence: 99%